Spontaneous Intracranial Hypotension: A Systematic Imaging Approach for CSF Leak Localization and Management Based on MRI and Digital Subtraction Myelography - Farb, R.I.; Nicholson, P.J.; Peng, P.W.; Massicotte, E.M.; Lay, C.; Krings, T.; terBrugge, K.G. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Localization of the culprit CSF leak in patients with spontaneous intracranial hypotension can be difficult and is inconsistently achieved. We present a high yield systematic imaging strategy using brain and spine MRI combined with digital subtraction myelography for CSF leak localization.MATERIALS AND METHODS: During a 2-year period, patients with spontaneous intracranial hypotension at our institution underwent MR imaging to determine the presence or absence of a spinal longitudinal extradural collection. Digital subtraction myelography was then performed in patients positive for spinal longitudinal extradural CSF collection primarily in the prone position and in patients negative for spinal longitudinal extradural CSF collection in the lateral decubitus positions.RESULTS: Thirty-one consecutive patients with spontaneous intracranial hypotension were included. The site of CSF leakage was definitively located in 27 (87%). Of these, 21 were positive for spinal longitudinal extradural CSF collection and categorized as having a ventral (type 1, fifteen [48%]) or lateral dural tear (type 2; four [13%]). Ten patients were negative for spinal longitudinal extradural CSF collection and were categorized as having a CSF-venous fistula (type 3, seven [23%]) or distal nerve root sleeve leak (type 4, one [3%]). The locations of leakage of 2 patients positive for spinal longitudinal extradural CSF collection remain undefined due to resolution of spontaneous intracranial hypotension before repeat digital subtraction myelography. In 2 (7%) patients negative for spinal longitudinal extradural CSF collection, the site of leakage could not be localized. Nine of 21 (43%) patients positive for spinal longitudinal extradural CSF collection were treated successfully with an epidural blood patch, and 12 required an operation. Of the 10 patients negative for spinal longitudinal extradural CSF collection (8 localized), none were effectively treated with an epidural blood patch, and all have undergone (n = 7) or are awaiting (n = 1) an operation.CONCLUSIONS: Patients positive for spinal longitudinal extradural CSF collection are best positioned prone for digital subtraction myelography and may warrant additional attempts at a directed epidural blood patch. Patients negative for spinal longitudinal extradural CSF collection are best evaluated in the decubitus positions to reveal a CSF-venous fistula, common in this population. Patients with CSF-venous fistula may forgo further epidural blood patch treatment and go on to surgical repair.CVFCSF-venous fistulaDSMdigital subtraction myelographyEBPepidural blood patchSIHspontaneous intracranial hypotensionSLECspinal longitudinal extradural CSF collectionSLEC-Nnegative for spinal longitudinal extradural CSF collectionSLEC-Ppositive for spinal longitudinal extradural CSF collection